Hieracium-associated aphid parasitoid guilds (Hymenoptera: Braconidae: Aphidiinae) in Europe - Tomanović, Šeljko; Starý, Petr; Kavallieratos, Nickolas G.; Petrović, Andjeljko; Niketić, Marijan; Vučetić, Andja (Zootaxa, 2008)
Eleven aphidiine braconid species are associated with 10 aphid species to form over 50 tritrophic associations in Europe. The host aphids belong to five genera, Aphis L., Brachycaudus Van der Goot, Hyperomyzus Börner, Nasonovia Mordvilko, and Uroleucon Mordvilko, and feed on 11 Hieracium species. Five new host plant records are reported. The associated aphidiine guilds are linked with the taxonomic position of the host aphids. Host aphids such as Brachycaudus helichrysi (Kaltenbach) and Uroleucon spp. are broadly oligophagous, but Nasonovia spp., Aphis hieracii Schrank, and Hyperomyzus hieracii (Börner) are specific mainly to Hieracium and related plants. A key for the identification of aphidiine species associated with aphids on Hieracium plants in Europe is provided.